Gender Matters in Hospitality (invited paper for 'luminaries' special issue of International Journal of Hospitality Management). (January 2019) - Morgan, Nigel; Pritchard, Annette
Abstract: This article is a review paper, which examines the place of gender in hospitality research and education and discusses the significance of hospitality for women's employment and entrepreneurship opportunities. The paper's main purpose, however, is to speculate on the future of hospitality gender research and women's employment prospects in the industry. It suggests that, despite the emergence of gender perspectives in hospitality research and the recent rise of popular feminism in response to high-profile sexual harassment cases and a well-publicised gender pay gap, gender still does not occupy mainstream territory in the field. The paper stresses the continued missed opportunities of neglecting female talent and calls on female and male leaders to shape a gender-just future in hospitality study and practice by mentoring and holding hierarchies to account. The paper identifies AI and robotics and sexual exploitation and harassment as two areas in which hospitality gender scholars could lead scholarship and policy debates on gendered human experiences.